2017
DOI: 10.1016/j.nicl.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection and visualisation of MEG ripple oscillations in epilepsy

Abstract: High frequency oscillations (HFOs, 80–500 Hz) in invasive EEG are a biomarker for the epileptic focus. Ripples (80–250 Hz) have also been identified in non-invasive MEG, yet detection is impeded by noise, their low occurrence rates, and the workload of visual analysis. We propose a method that identifies ripples in MEG through noise reduction, beamforming and automatic detection with minimal user effort. We analysed 15 min of presurgical resting-state interictal MEG data of 25 patients with epilepsy. The MEG s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 42 publications
(72 reference statements)
0
35
0
Order By: Relevance
“…All patients showed icEEG ripples. The icEEG-ripplezone included 33 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) contacts with mean rate of 9.8 (6.3-14.3) ripples/min. Of all the ripple sources within icEEG coverage, 79% for ESI and 83% for MSI were concordant to the icEEG-ripple-zone, without difference between lesional and nonlesional patients (ESI: P = 0.8; MSI: P = 0.5).…”
Section: Concordance Of Ripple Sources With Iceegmentioning
confidence: 99%
See 3 more Smart Citations
“…All patients showed icEEG ripples. The icEEG-ripplezone included 33 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) contacts with mean rate of 9.8 (6.3-14.3) ripples/min. Of all the ripple sources within icEEG coverage, 79% for ESI and 83% for MSI were concordant to the icEEG-ripple-zone, without difference between lesional and nonlesional patients (ESI: P = 0.8; MSI: P = 0.5).…”
Section: Concordance Of Ripple Sources With Iceegmentioning
confidence: 99%
“…Previous studies showed that noninvasively localized ripple generators correlate with regions generating interictal spikes or with different approximations of the EZ defined by clinical information . However, most of these studies included patients who did not necessarily undergo surgery, with the exception of two MEG studies on patients with focal MRI lesions or insular epilepsy .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MEG studies from different centers suggest that it is possible to detect isolated FO events from interictal MEG recordings with satisfactory data quality [von Ellenrieder et al, 2016; van Klink et al, 2016a; Papadelis et al, 2016]. Four studies validated FO localization against the postsurgical cavity in good outcome patients as gold standard for the EZ; they point towards usefulness of FOs for delineating the EZ [van Klink et al, 2017; Velmurugan et al, 2019; Yin et al, 2019; Tamilia et al, 2020].…”
Section: Introductionmentioning
confidence: 99%